Graphene and Iron based composites as EMI shielding: A Systematic Review - Ayub, S. (Institute of Electrical and Electronics Engineers Inc., 2020)
The electromagnetic inference is a problem for a longer span. Various composites were formed to eliminate this problem by developing electromagnetic shielding material. For this purpose, a systematic review was performed to provide a general understanding of graphene and iron-based composites as a shielding material. Scopus database was selected to extract the articles with the only limitation to consider only those articles which were written in the English language. The interpretation of the articles revealed that most of the researchers have worked on the X-band frequency range, where still, there is a need to work on a higher frequency range. Also, the inclusion of polymers into graphene and iron showed promising results, yet still, need further exploration. Â© 2020 IEEE.